2022
DOI: 10.3390/brainsci12050675
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment and Preoperative Neutrophil-to-Lymphocyte Ratio Predicts Prognostic Value of Glioblastoma: A Meta-Analysis

Abstract: Objective: Although some meta-analyses have shown a correlation between a high neutrophil-to-lymphocyte ratio (NLR) and low survival in patients with gliomas, their conclusions are controversial, and no study has specifically explored the relationship between a high pre-treatment and pre-operative NLR and low survival in patients with glioblastoma (GBM). Therefore, we further investigated this correlation through meta-analysis. Methods: We searched the PubMed, Metstr, and Cochrane databases in March 2022 for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Finally, there is increasing evidence, based on studies using large sample sizes, that suggests that both a high pre-treatment and preoperative NLR are correlated with poor overall survival in GBM patients. This aligns with the conclusions from our results [11,12].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, there is increasing evidence, based on studies using large sample sizes, that suggests that both a high pre-treatment and preoperative NLR are correlated with poor overall survival in GBM patients. This aligns with the conclusions from our results [11,12].…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies corroborate the prognostic significance of elevated levels of the NLR and PLR before surgery [10][11][12]. Conversely, the role of the RDW as a prognostic indicator has been a subject of divergence.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…High baseline (preoperative/pretreatment) NLR was established as an independent predictor of shorter overall survival in patients with glioblastoma/gliomas (Table 1) (51, 52, 54, 56-59, 85, 90-92, 112, 114, 119-128), and this was confirmed by meta-analyses (131)(132)(133). However, the independent prognostic significance of NLR remains debatable (55).…”
Section: A High Neutrophil-to-lymphocyte Ratio Is a Prognostic Factor...mentioning
confidence: 92%
“…A comparison made between these hematological markers and traditional molecular prognostic markers demonstrated that isocitrate dehydrogenase-1 mutation in gliomas was associated with chronic low-grade inflammation, which could be associated with a better prognosis in this subgroup of patients [ 28 ]. Recently, four meta-analyses demonstrated that NLR could be considered a prognostic factor in GMB, and some modification of chemotherapy should be recommended in high-risk patients [ 29 , 30 , 31 , 32 ]. In our retrospective study, we turned our attention to systemic inflammatory-immune markers, NLR, SII, and SIRI, which are based on neutrophil counts and which all exceeded the reference values proposed by Luo et al [ 33 ] and Qui et al [ 34 ] (0.87–4.15 103/µL for NLR, 142–808 103/µL for SII and 0.41–1.42 103/µL for SIRI).…”
Section: Introductionmentioning
confidence: 99%